KONJUNGSI DALAM KALIMAT MAJEMUK SISWA KELAS X SMK (STUDI KASUS MULTISITUS) - Dwi Angga Septianingrum; Sumadi Sumadi; Sunaryo Sunaryo (Graduate School of Universitas Negeri Malang, 2016)
This research is conducted to describe conjunction in compound sentences by first year students of vocational high school, particulary to describe forms, types, and senses in compound sentences written by vocational high school’s student. Forms, types, and senses of conjungtions in this research include (1) forms, types, and senses of conjungtions in compound sentence and (2) forms, types, and senses of conjungtions in complex sentence. This research adopted qualitative approach design with multiple-site case study based. The research results are form, types, and senses of conjungtions in compound sentences from sites I and sites II which have different.Penelitian ini bertujuan untuk mendeskripsikan konjungsi dalam kalimat majemuk siswa kelas X SMK, khususnya mendeskripsikan wujud, jenis, dan makna konjungsi dalam kalimat majemuk siswa SMK. Wujud, jenis, dan makna konjungsi dalam penelitian ini meliputi (1) wujud, jenis, dan makna konjungsi dalam kalimat majemuk setara kelas X SMK dan (2) wujud, jenis, dan makna konjungsi dalam kalimat majemuk bertingkat siswa kelas X SMK. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan penelitian studi kasus multisitus. Hasil penelitian adalah wujud, jenis, dan makna konjungsi dalam kalimat majemuk situs I dan situs II memiliki kekhasan yang berbeda.